2023
DOI: 10.3847/1538-4357/acd4ba
|View full text |Cite
|
Sign up to set email alerts
|

The Nonorthogonal X-line in a Small Guide-field Reconnection Event in the Magnetotail

Abstract: Magnetic reconnection is a fundamental plasma process that has been studied with analytical theory, numerical simulations, in situ observations, and laboratory experiments for decades. The models that have been established to describe magnetic reconnection often assume a reconnection plane normal to the current sheet in which an antiparallel magnetic field annihilates. The annihilation points, also known as the X-points, form an x-line, which is believed to be perpendicular to the reconnection plane. Recently,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 73 publications
1
4
0
Order By: Relevance
“…One feature to note is that the X-line is not parallel to M but oblique to it (Figures4k-4n, which shows the reconstruction in the LM plane of the current sheet). A similar slanted X-line was recently observed byPathak et al (2022) andQi et al (2023). As a consequence, the position of the X-line depends on M and the choice of the appropriate M plane for the reconstruction is therefore crucial.…”
supporting
confidence: 73%
“…One feature to note is that the X-line is not parallel to M but oblique to it (Figures4k-4n, which shows the reconstruction in the LM plane of the current sheet). A similar slanted X-line was recently observed byPathak et al (2022) andQi et al (2023). As a consequence, the position of the X-line depends on M and the choice of the appropriate M plane for the reconstruction is therefore crucial.…”
supporting
confidence: 73%
“…(2022) examined this issue for an MMS event and reported that the direction of least gradient was tilted between 40° and 60° from e M as defined above, and their work motivated our study (See also work by Qi et al. (2023). ).…”
Section: Introductionmentioning
confidence: 84%
“…For the purposes of a 2D description, the minimum gradient would ideally be orthogonal to the reconnection plane, L-N; so an L-N plane defined using MVA may not best represent the plane of predominant spatial variation. Recently Pathak et al (2022) examined this issue for an MMS event and reported that the direction of least gradient was tilted between 40° and 60° from e M as defined above, and their work motivated our study (See also work by Qi et al (2023). ).…”
mentioning
confidence: 89%
“…Turbulence, however, adds difficulty in establishing the LMN system, which is vital for determining EDR characteristics. Here, we follow a process outlined in Qi et al (2023). The N direction is derived from the maximum variance of E and from the maximum directional derivative of B and E. N is derived repeatedly using low-pass filters of 1, 2, and 4 Hz, employing time periods centered on the EDR (∼04:38:58.5) of 2, 4, and 8 s, and isolating the most active components of B and E. The 36 derived values are in good agreement with a standard deviation of less than 5°.…”
Section: Observationmentioning
confidence: 99%
“…The position of MMS1 in N is derived from Ampere's law. Starting from J M ∼ ∂B L /∂N − ∂B N /∂L, ΔN can be written as Pathak et al 2022 andQi et al 2023 for details). B N (Figure 3(a)) has a small and nearly constant slope suggesting a smooth progression in L so ∂B N /∂L is a small correction.…”
Section: Observationmentioning
confidence: 99%